2003
DOI: 10.1007/s00247-003-0896-7
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of kidneys: functional evaluation using F-15 perfusion imaging

Abstract: Dynamic contrast-enhanced MR urography provides superior anatomic and functional information when compared with ultrasound and diuretic renal scintigraphy. The information is gathered in a single study that does not use ionizing radiation. It is likely that MR urography will replace renal scintigraphy in the evaluation of hydronephrosis in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
13

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(56 citation statements)
references
References 29 publications
2
41
0
13
Order By: Relevance
“…Identification of VUR is important because children with concurrent VUR and PUJ obstruction may be at higher risk for severe infection. Magnetic Resonance Imaging (MRI) with urography is being investigated to define urinary tract anatomy, calculate differential renal function, and assess urinary tract obstruction [8].…”
Section: Discussionmentioning
confidence: 99%
“…Identification of VUR is important because children with concurrent VUR and PUJ obstruction may be at higher risk for severe infection. Magnetic Resonance Imaging (MRI) with urography is being investigated to define urinary tract anatomy, calculate differential renal function, and assess urinary tract obstruction [8].…”
Section: Discussionmentioning
confidence: 99%
“…It is the lack of our study that single kidney GFR could not be calculated because of technical insufficiencies. Some previous studies reported that DRF on MRU was in correlation with SRF on DRS (4,5) . We have also determined a significant correlation between DRF and SRF, and our data suggest that each procedure is useful in the determination of renal function.…”
Section: Discussionmentioning
confidence: 88%
“…Superior spatial and contrast resolution is achieved with dynamic contrast enhanced MRU compared to that of USG or DRS (4). Analysis of renal function with MRU is comparable to that of DRS (4,5). The quality of dynamic MR images enables additional functional parameters to be derived, such as renal transit time (RTT) (6).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] One disadvantage of these conventional gradient-echo sequences regarding applications in young children is, however, the relatively long acquisition time of approximately 5-15 s resulting in breathing artefacts. In this study, we evaluate a protocol applying a singleshot TurboFLASH sequence with an acquisition time of only 0.5 s, which can be combined with a navigator-triggering technique providing images at virtually identical diaphragm positions.…”
Section: Advances In Knowledgementioning
confidence: 99%